Pro-poor risk reduction strategy for HPAI control in backyard poultry in Indonesia: a project overview and approaches used - Unger, Fred; Mariner, Jeffrey C.; Narrod, C.; Syafrison, I.; Sudarman, A.; Arifin, B.; Nuryartono, N.; Sumiarto, B.; Siregar, E.S. (International Livestock Research Institute, 2009)
Considering that Highly Pathogenic Avian Influenza (HPAI) in developing countries is not solely a veterinary problem, especially in backyard flocks, and an acceptable control can only be successful with the involvement of those small holders a research agenda was developed by an international expert team in collaboration with national partners from four African countries (Nigeria, Kenya, Ethiopia, Ghana) and Indonesia. The team includes veterinary and economic scientists. Despite significant scientific advances made towards understanding of HPAI, knowledge gaps remain on e.g. disease epidemiology and economic impact of HPAI and its control with specific emphasis on the effects of alternative mitigation strategies on livelihoods. Moreover, there is a limited understanding of the institutional arrangements most suited for disease control in different production systems. To address the knowledge gaps several components were developed and implemented in all five countries consisting of (a) Risk assessment, (b) Livelihood and (c) Institutional analysis. A planned cross-country analysis will allow to identify similarities and differences in HPAI control and its success between the project countries. The submitted paper will present used approaches for each research component with special emphasis on implemented activities in Indonesia, a country where HPAI is considered to be endemic in many parts of the country and conventional control measures have failed to limit substantially the spread of the disease. Beside of this a situation overview on HPAI will be provided.